DAMPAK TATA KELOLA PERUSAHAAN YANG BAIK DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Saputra, Ferdyan Wana; Cahyani, Mita (JAB (Jurnal Akuntansi & Bisnis), 2025)
This research aims to determine the influence of Good Corporate Governance and company size on company value. The proxy for company value is price to book value (PBV).TheindicatorsusedinGoodCorporateGovernanceincludemanagerialownership and institutional ownership, while company size uses a proxy for total assets. The populationinthisresearchwas28oilpalmplantationcompanieslistedontheIndonesia Stock Exchange (BEI) in 2018-2022 and a final sample of 11 companies was obtained using the Purposive Sampling method. Researchers used multiple linear regression analysis techniques. The research results simultaneously show that Good Corporate Governance with indicators of managerial ownership and institutional ownership and company size have a significant effect on company value. The partial research results show that Good Corporate Governance with indicators of managerial ownership and institutionalownershiphasasignificantnegativeeffectoncompanyvalueandcompany size has a significant negative effect on company value